Religious Moderation in the Context of Integration between Religion and Local Culture in Indonesia - Fuadi, Moh. Ashif; Faishol, Abd; Rifa’i, Andi Arif; Triana, Yunika; Ibrahim, Rustam (Journal of Al-Tamaddun, 2024)
This study analyzes the historical flow of Islamic indigenization to Religious Moderation (wasaṭiyah). With qualitative methods and literature study approaches, this study concluded that firstly, Islamic Pribumization is the result of the thoughts of K.H. Abdurrahman Wahid (Gus Dur), Islam Nusantara initiated by K.H. Said Aqil Siradj and Religious Moderation by Lukman Hakim Saifuddin which was motivated by his response to the trend of Arabization, Fundamentalism and Islamic Radicalism in Indonesia. Secondly, the discourse of Islamic Pribumization and Islam Nusantara has similarities; both use the methodologies of al-’ādah muḥakkamah and al-’tsābit bi al-’urf ka al-tsābit bi al-naṣ which are considered capable of paying attention to the needs that exist in local culture. Meanwhile, Religious Moderation is a top-down policy by the government under the Ministry of Religious Affairs to maintain religious harmony by applying a moderate religious perspective. All three have the same characteristics of affirming moderate Islamic principles, upholding tolerance, and maintaining local wisdom. Thirdly, based on the historical flow and contextualization of religious values with culture, the concept of Islamic Indigenization has substantially shifted to be adopted by the concept of Islam Nusantara and now represents it as one of the indicators of religious moderation, namely accommodating local culture so that it has strong relevance. This research shows the relationship between the historical flow of Islamic indigenization, Islam Nusantara, and Religious Moderation, which seeks to create a dialogue between religion and culture.